Peripheral blood lymphocyte phenotype of ZAP-70⁺ and ZAP-70⁻ patients with B-cell chronic lymphocytic leukaemia - Rivkina, A.; Kholodyuk I. Holodnuka; Murovska, M.; Soloveichika, M.; Lejniece, S. (Experimental Oncology, 2015)
Background: Up to now, the immune status of chronic lymphocytic leukemia (CLL) patients in association with the expression of zeta-chain-associated protein kinase 70 (ZAP-70) in leukemic cells has not been evaluated. Aim: The aim of this work was the study of the peripheral blood (PB) T-lymphocyte phenotypes in ZAP-70-positive (ZAP-70⁺) and ZAP-70-negative (ZAP-70⁻) untreated patients with CLL. Materials and Methods: ZAP-70⁻, CD25-, CD3-, CD4-, and CD8-positive lymphocytes were enumerated by flow cytometry in PB of 120 untreated CLL patients. CD8+, CD3+CD4+ and CD3+CD25+ cells were counted for the non-leukemic lymphocytes. Results: The patients were distributed into two groups: the ZAP-70⁺ group of high CLL progression (n = 61), and the ZAP-70− group of low CLL progression (n = 59). In the ZAP-70⁺ group, the ratio CD4/CD8 (0.33 ± 0.62; p = 0.001) and the numbers of the CD3+ (34.8 ± 8.1%; p = 0.01), CD3+CD4+ (24.4% ± 4.8; p = 0.001), and CD3+CD25+ (6.2 ± 0.91%; p = 0.001) lymphocytes were reduced and the percentage of the CD8+ cells (73.1 ± 4.6%; p = 0.0001) was above the norm. In the ZAP-70− group, the number of the CD3+CD4+ cells (36.9 ± 6.1%; p = 0.001) was within the norm, but the numbers of the CD8+ (11.3 ± 1.1%; p = 0.0001) and CD3+ (41.2 ± 5.3%; p = 0.05) lymphocytes were reduced; the ratio CD4/CD8 (3.26 ± 0.88; p = 0.001) and the percentage of the CD3+CD25+ cells (27.1 ± 3.4%; p = 0.0001) were above the norm. Conclusions: Our data show that the increased CD4/CD8 ratio, caused by the reduced number of the CD8+ lymphocytes, and the increased number of CD3+CD25+ cells are characteristic for the ZAP-70− group (slow progressing) of untreated CLL patients. In ZAP-70⁺ patients, the CD4/CD8 ratio was significantly below the norm indicating an active disease process. Results of our study contribute to identification of CLL patients with different prognosis in routine diagnostic/prognostic procedures. Key Words: chronic lymphocytic leukemia, ZAP-70, immune status, CD4/CD8 ratio, regulatory T cell.